2011
DOI: 10.1242/jcs.079830
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin is required for efficient Rap1-induced cell spreading

Abstract: SummaryThe Rap family of small GTPases regulate the adhesion of cells to extracellular matrices. Several Rap-binding proteins have been shown to function as effectors that mediate Rap-induced adhesion. However, little is known regarding the relationships between these effectors, or about other proteins that are downstream of or act in parallel to the effectors. To establish whether an array of effectors was required for Rap-induced cell adhesion and spreading, and to find new components involved in Rap-signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 69 publications
4
44
0
Order By: Relevance
“…2B). Membrane translocation of Epac1 by ERM proteins cooperates with its DEP domain-mediated translocation (Gloerich et al, 2010) and is required for Rap-induced cell adhesion and spreading (Ross et al, 2011). The DEP domain targets Epac1 uniformly to the plasma membrane, whereas ERM targets Epac1 to plasma membrane clusters (Gloerich et al, 2010), implicating different biologic outcomes of Epac1 targeting by either the DEP domain or ERM.…”
Section: Spatial Regulation Of Epacmentioning
confidence: 99%
See 1 more Smart Citation
“…2B). Membrane translocation of Epac1 by ERM proteins cooperates with its DEP domain-mediated translocation (Gloerich et al, 2010) and is required for Rap-induced cell adhesion and spreading (Ross et al, 2011). The DEP domain targets Epac1 uniformly to the plasma membrane, whereas ERM targets Epac1 to plasma membrane clusters (Gloerich et al, 2010), implicating different biologic outcomes of Epac1 targeting by either the DEP domain or ERM.…”
Section: Spatial Regulation Of Epacmentioning
confidence: 99%
“…The DEP domain targets Epac1 uniformly to the plasma membrane, whereas ERM targets Epac1 to plasma membrane clusters (Gloerich et al, 2010), implicating different biologic outcomes of Epac1 targeting by either the DEP domain or ERM. Direct interaction of Epac1 with either ezrin, radixin, or moesin may play a role in cell adhesion per se, because deletion of the N-terminal 49 amino acid of Epac1 and Epac1 displacement from ERM with the actin binding domain of radixin reduce Epac1-dependent cell adhesion (Gloerich et al, 2010;Ross et al, 2011). Additional recent studies indicate that thyroid-stimulating hormonemediated and cAMP-dependent mitogenesis requires assembly of both Epac and PKA to a radixin scaffold, a process dependent on the DEP domain of Epac1 (Hochbaum et al, 2008(Hochbaum et al, , 2011.…”
Section: Spatial Regulation Of Epacmentioning
confidence: 99%
“…In addition, EPAC proteins exert their functions through interactions with other cellular partners at specific cellular loci. For example, EPAC1 is known to associate with mitotic spindle, plasma membrane, and nuclear membrane by interacting with tubulin Mei and Cheng, 2005), ezrin-radixin-moesin (ERM) proteins Ross et al, 2011), and nucleoporin RanBP2 (Liu et al, 2010;Gloerich et al, 2011), respectively. On the other hand, EPAC2 can interact with Rim (Rab3 interacting molecule) and Rim2 (Ozaki et al, 2000;Kashima et al, 2001), as well as a structurally related calcium sensor Piccolo (Fujimoto et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Because activation of cAMP-GEFs induced cell spreading in renal epithelial cells (supplementary material Fig. S3D) (Ross et al, 2011), Rap signaling must also be enhanced and contribute to the pathogenesis of PKD. Because membrane polarity proteins, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Because Rap2 has been reported to activate ezrin (Gloerich et al, 2012), one of the ERM family proteins that bind F-actin and are involved in the regulation of cell spreading (Bretscher et al, 2002;Ross et al, 2011), and because increased phosphorylation of ezrin (active form) was shown in confluent Slp2-a-KD cells in our previous study , we hypothesized that the increased Rap2 activity in subconfluent Slp2-a-KD cells also activates ezrin. The results of the immunoblot analysis showed a clear increase in ezrin phosphorylation in the subconfluent Slp2-a-KD cells in comparison with the control MDCK II cells (Fig.…”
Section: Ezrin Is Activated In Slp2-a-kd Cellsmentioning
confidence: 93%